# Y+2=-3(x-4)?

• Y+2=-3(x-4)?  Anonymous748916 | 03/12 2020 07:18 creative college essays i need help with statistics homework essay writing for college students
Positive: 100 %
Answer #2 | 10/10 2016 15:33 From your question Y + 2 = -3(x - 4) = -3(x - 4) = -3x + 12 = -3x + 10 + 2 Let Y = -3x + 10 = Y + 2 = (-3x + 10) + 2 Hence = Y + 2 = ( -3x + 10) + 2
Positive: 66.666666666667 %
Answer #3 | 10/10 2016 20:11 y = - 3x + 10
Positive: 66.666666666667 %
Answer #4 | 10/10 2016 08:28 y + 2 = -3(x − 4) <== This is a line in point-slope form. with a slope of m = -3 and passes though the point (4,-2) [ y − y₁ = m(x − x₁) ] ∴ y + 2 = -3x + 12 ∴ y = -3x + 10 <== the same line in slope-intercept form [ y = mx + b ] ∴ 3x + y = 10 <== the same line in standard form [ Ax + By = C ] ∴ 3x + y − 10 = 0 <== the same line in general form [ Ax + By + C = 0 ] the real question is what do want us to to do with the line. we can tell you the line crosses the y-axis at (0,10) and the x-axis at (10/3,0) and has a slope (aka gradient) of -3
Positive: 60 %
Answer #5 | 10/10 2016 13:11 y = - 3x + 10
Positive: 60 %
Answer #6 | 10/10 2016 15:23 y = -3x + 10 <<< slope intercept form
Positive: 50 %
Anonymous353844 | 03/12 2020 04:57 model essay writing analysis section of research paper essay writing for scholarship
Positive: 50 %
Anonymous446639 | 01/12 2020 03:13 essay strategies my essay quotes on essay writing
Positive: 50 %
Answer #9 | 10/10 2016 15:28 y + 2 = -3(x − 4) <== This is a line in point-slope form. with a slope of m = -3 and passes though the point (4,-2) [ y − y₁ = m(x − x₁) ] ∴ y + 2 = -3x + 12 ∴ y = -3x + 10 <== the same line in slope-intercept form [ y = mx + b ] ∴ 3x + y = 10 <== the same line in standard form [ Ax + By = C ] ∴ 3x + y − 10 = 0 <== the same line in general form [ Ax + By + C = 0 ] the real question is what do want us to to do with the line. we can tell you the line crosses the y-axis at (0,10) and the x-axis at (10/3,0) and has a slope (aka gradient) of -3
Positive: 37.5 %
Answer #10 | 10/10 2016 08:23 y = -3x + 10 <<< slope intercept form
Positive: 40 %
Answer #11 | 10/10 2016 08:33 From your question Y + 2 = -3(x - 4) = -3(x - 4) = -3x + 12 = -3x + 10 + 2 Let Y = -3x + 10 = Y + 2 = (-3x + 10) + 2 Hence = Y + 2 = ( -3x + 10) + 2
Positive: 40 %
Anonymous27799 | 29/11 2020 23:00 thesis statements for persuasive essays thesis statement creator for research paper homework help australia 